High‐Performance Bifunctional Metasurfaces in Transmission and Reflection Geometries. Issue 2 (15th November 2016) - Cai, Tong; Tang, ShiWei; Wang, GuangMing; Xu, HeXiu; Sun, ShuLin; He, Qiong; Zhou, Lei
Abstract : Achieving multiple diversified functionalities in a single flat device is crucial for electromagnetic (EM) integration, but available efforts suffer the issues of device thickness, low efficiency, and restricted functionalities. Here, a general strategy to design high‐efficiency bifunctional devices based on metasurfaces composed by anisotropic meta‐atoms with polarization‐dependent phase responses is described. Based on the derived general criterions, two bifunctional metadevices, working in reflection and transmission modes, respectively, that can realize two distinct functionalities with very high efficiencies (≈90% in reflection geometry and ≈72% in transmission one) are designed and fabricated. Microwave experiments, including both far‐field and near‐field characterizations, are performed to demonstrate the predicted effects, which are in excellent agreement with numerical simulations. The findings in this study can motivate the realizations of high‐performance bifunctional metadevices in other frequency domains and with different functionalities, which are of crucial importance in EM integration. Abstract : A general strategy to design high‐efficiency bifunctional devices based on metasurfaces is proposed in this paper. As a proof of concept, it is experimentally demonstrated that two bifunctional metadevices working in reflection and transmission modes, respectively, can achieve two distinct functionalities (such as focusing and beam bending effect) with very high efficiency.